TOPOGRAFO THE PLACE AND ROLE OF GEODESIC AND CARTOGRAPHIC WORK IN THE NATIONAL ECONOMY - Abdukadirova Muharram Arabboyevna (Western European Studies, 2024)
Information is provided on topografo –geodesic and cartographic work performed in our country, topografo –geodesic and cartographic work performed in geodesic organizations, Organization of Topografo –geodesic and cartographic work on expeditions, Organization of Topografo –geodesic and cartographic work in parties, Organization of Topografo –geodesic and cartographic work in Brigades
Keywords: Topography; Geodesy; cartography